Endodontic clinical management of anatomical variation “C” shaped root canal type IV in a second mandibular molar - Llanos Carazas, Mónica Yizely (2019)
The C-shaped root canal system is an anatomical variation usually found in second mandibular molar with fused roots, present a transverse morphology that describes an arc of 180º or more, with a single taped hole orifice. The present clinical case describes the endodontic treatment with last generation equipments of a mandibular molar with C- shaped type IV and fork at apical level in a male patient that has pain to percussion, palpation and the topographic Cone Beam Tomography (CBCT) examination confirms the anatomical variation of the tooth code 47. The diagnosis was previously initiated treatment with symptomatic apical periodontitis. The retreatment of the canals using the preflaring before using the Reciproc® System R25, for the biomechanical preparation technique, calcium hydroxide root canal medication was prescribed for 7 days, sodium hypochlorite as passive irrigation with and continuous heat wave obturation technique beefill 2 in 1 hermetically sealing in apical zone. The control after three years shows the success of technology during the diagnosis and treatment in orden to increase the probability of long term success.